Figure 4 in A further study on littoral ciliates (Protozoa, Ciliophora) near King George Island, Antarctica, with description of a new genus and seven new species - Wilbert, Norbert; Song, Weibo (Zenodo, 2008)
Figure 4. Bickella antarctica nov. spec. (A–E) from life (A) and after protargol impregnation. (C) Lateral view, arrow marks the macronucleus. (E) Apical view, arrow marks the paroral membrane, arrowheads indicate the end of adoral-zone of membranelles. (D) Details of membranelles and paroral membrane. (B) Somatic kineties, composed of dikinetids. Scale bars: 100 Mm (A); 50 Mm (C); 20 Mm (E). : Published as part of Wilbert, Norbert & Song, Weibo, 2008, A further study on littoral ciliates (Protozoa, Ciliophora) near King George Island, Antarctica, with description of a new genus and seven new species, pp. 979-1012 in Journal of Natural History 42 (13-14) on page 989, DOI: 10.1080/00222930701877540, http://zenodo.org/record/5219160